Evaluating the effects of selective laser sintering processing parameters on the melt pool dimensions of tungsten carbide through numerical thermal modeling - Olivier, Carlo Martin (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.